The Influence of Price, Electronic Word Of Mouth (E-WOM), Discount and Tagline "Free Shipping" on Purchase Decisions at Shopee Market Place (Case Study on Students at the Faculty of Economics and Business, Labuhanbatu University) - Aulia Sekar Pramesti; Bayu Eko Broto; Bhakti Helvi Rambe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Online shopping has become a new habit in today's society and has even penetrated students. Developments in the field of technology have led to changes in students who used to only shop directly or offline now shopping online, including Universitas Labuhanbatu students. The survey method focuses on collecting data from respondents to make it easier for researchers to get the information they need. In this study, the population was students of the Faculty of Economics and Business, Universitas Labuhanbatu. This study used a purposive sampling technique, with a total sample of 50 people. Data collection techniques used a questionnaire with a Likert scale. This study shows that there is a positive effect of price on purchasing decisions, there is a positive influence of E-wom on purchasing decisions, there is a positive influence of discount on purchasing decisions, and there is a positive influence of the tagline "Gratis Ongkir" on purchasing decisions. Price, E-wom, discount, and the tagline "Gratis Ongkir" together have a positive and significant effect on purchasing decisions.